Highly doubly excited states of helium under periodic driving and the formation of nondispersive wave packets (2018)
We provide a full characterization of two-electron nondispersive wave packets found in the Floquet spectrum of driven helium. These quantum objects which propagate along periodic trajectories of the classical three-body Coulomb problem without dispersion have been identified early within large numerical calculations on one- and two-dimensional models. In this thesis, we present an efficient treatment to describe the dynamics of doubly excited states of helium under electromagnetic driving. With this approach, we are able to identify the resonance states of helium that play the fundamental role in the formation of these nondispersive wave packets, which allows us to give for the first time, theoretical evidence of their existence in three-dimensional helium. Furthermore, we compute the entanglement of doubly excited states of planar helium. We also discuss the effect of a periodic driving by an external field on entanglement. In particular, we focus on the entanglement of two-electron nondispersive wave packets.